Peran Penerapan Electronic Procurement Pengadaan Barang Dan Jasa Pemerintah Untuk Mencegah Fraud Pada Biro Administrasi Pembangunan Dan Pengadaan Barang/Jasa Provinsi Kalimantan Barat - Dewi, Vita (FAKULTAS EKONOMI DAN BISNIS UNTAN, 2019)
Manual procurement has triggered a lot of fraud. During the period 2004 to 2010, the Corruption Case for Procurement of Goods/Services handled by the KPK had reached 44%. The purpose of this study was to find out and analyze the implementation of government procurement of goods and services through electronic procurement and to find out and analyze the role of electronic procurement to prevent fraud at the Goods/Services Procurement and Development Administration Bureau. The method used is a qualitative method with data collection techniques in field observation, interviews, and documentation studies. Research Subjects are the Head of the Development Administration and Goods/Services Procurement Bureau, Head of the Goods/Services Procurement Section, Sub Head of the Goods/Services Procurement Section, the Auction Committee and the Bidder in West Kalimantan Province.Â The results of this study prove that the implementation using electronic procurement systems has been going well while the role of electronic procurement to prevent fraud has succeeded in contributing to fraud prevention besides that the process of procuring goods and services becomes more transparent, open and creates fair competition.